2016
DOI: 10.1002/mabi.201600281
|View full text |Cite
|
Sign up to set email alerts
|

Super-Anticoagulant Heparin-Mimicking Hydrogel Thin Film Attached Substrate Surfaces to Improve Hemocompatibility

Abstract: In this study, heparin-mimicking hydrogel thin films are covalently attached onto poly(ether sulfone) membrane surfaces to improve anticoagulant property. The hydrogel films display honeycomb-like porous structure with well controlled thickness and show long-term stability. After immobilizing the hydrogel films, the membranes show excellent anticoagulant property confirmed by the activated partial thromboplastin time values exceeding 600 s. Meanwhile, the thrombin time values increase from 20 to 61 s as the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 63 publications
(92 reference statements)
0
20
0
Order By: Relevance
“…To attach hydrogel layer onto membrane surface, the key point is to introduce anchoring sites for the hydrogel layer. In our previous studies, in situ crosslinking polymerization of 2‐hydroxyethyl methacrylate (HEMA) in PES solution was applied to introduce hydroxyl groups onto the surface as the anchoring points . However, it might cause the microstructure change, which would usually deteriorate the membrane performance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To attach hydrogel layer onto membrane surface, the key point is to introduce anchoring sites for the hydrogel layer. In our previous studies, in situ crosslinking polymerization of 2‐hydroxyethyl methacrylate (HEMA) in PES solution was applied to introduce hydroxyl groups onto the surface as the anchoring points . However, it might cause the microstructure change, which would usually deteriorate the membrane performance.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Zhao et al immersed double bonds grafted PES membrane into hydrogel precursor solution, then a free radical crosslinking polymerization was conducted to form a hydrogel thin film onto the surface . In our previous works, we developed a simple technique to covalently attach functional hydrogel thin layers onto polyethersulfone (PES) membrane surfaces, and super‐anticoagulant and robust antibacterial surfaces were prepared …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in comparison with common hemocompatibility approaches, hydrogelbased techniques could be significantly efficient. A support for such a hypothesis is a research reported by [86] who immobilized a heparin-mimicking thin film hydrogel on PES hemodialysis membrane which resulted in three times higher clotting time than best modified blood purification membranes (activated partial thromboplastin time value of 600 sec).…”
Section: Hemocompatibility Enhancementsmentioning
confidence: 94%
“…Nonspecific protein adsorbed on the surface of vascular grafts can induce biomaterialassociated clotting or platelet adhesion and activation. [24] Low nonspecific protein adsorption is crucial for vascular grafts to prevent thrombosis, especially fibrinogen adsorption. [25] Pure PVA tubes showed adsorption amounts of albumin and fibrinogen of 2.1 and 2.8 μg cm −2 (Figure 3a), which were attributed to the high hydrophilicity of PVA tubes that prevented protein adsorption.…”
Section: Protein Adsorptionmentioning
confidence: 99%